PENDIDIKAN AKHLAK; TELAAH PEMIKIRAN MENURUT AL-GHAZALI - Siti Masitoh; Acih Sunarsih; Audi Imani; Siti Fatimah; Jajang; Suci Dwi Handayani (Cakrawala Pedagogik, 2026)
Moral education is the main foundation in the Islamic education system, which aims to develop individuals who are not only intellectually intelligent, but also morally and spiritually noble. In the modern context, the moral crisis caused by globalization, materialism, and the degradation of values highlights the urgency of reinforcing moral education as a counterbalance to technological and scientific progress. This study aims to examine Imam Al-Ghazali's thoughts on moral education as a conceptual solution to today's moral challenges. Using a qualitative approach through a literature study of Al-Ghazali's works such as Ihya 'Ulum al-Din, Ayyuha al-Walad, and Mizan al-'Amal, this study highlights the importance of education as a process of character building through the internalization of spiritual values and the habit of righteous deeds. Al-Ghazali emphasized that true education must include purification of the soul (tazkiyatun nafs) and the formation of noble morals, not merely the transfer of knowledge. The results of the study show that Al-Ghazali's thoughts are still very relevant in designing an integral and applicable moral education curriculum, and can be a model for character building among the younger generation amid the challenges of the times.